2018
DOI: 10.1007/s12035-018-1169-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Curcumin Against Ischemia-Reperfusion Injury in the Nervous System

Abstract: Ischemia-reperfusion injury (I/R injury) is a common feature of ischemic stroke which occurs when blood supply is restored after a period of ischemia. Although stroke is an important cause of death in the world, effective therapeutic strategies aiming at improving neurological outcomes in this disease are lacking. Various studies have suggested the involvement of different mechanisms in the pathogenesis of I/R injury in the nervous system. These mechanisms include oxidative stress, platelet adhesion and aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 172 publications
2
56
0
Order By: Relevance
“…Mice lacking eNOS expression have previously been shown to exhibit a larger infarcted area in the brain following ischemia relative to wild‐type controls, with eNOS also being known to be essential as a regulator of cell proliferation and apoptosis . In this study, we found that endothelial cells rapidly induced eNOS following cerebral IRI (Figure ), with Sphk1/S1P being essential mediators of NO generation and angiogenesis in an eNOS‐dependent manner in an HBMEC model of OGDR (Figures ).…”
Section: Discussionsupporting
confidence: 53%
“…Mice lacking eNOS expression have previously been shown to exhibit a larger infarcted area in the brain following ischemia relative to wild‐type controls, with eNOS also being known to be essential as a regulator of cell proliferation and apoptosis . In this study, we found that endothelial cells rapidly induced eNOS following cerebral IRI (Figure ), with Sphk1/S1P being essential mediators of NO generation and angiogenesis in an eNOS‐dependent manner in an HBMEC model of OGDR (Figures ).…”
Section: Discussionsupporting
confidence: 53%
“…A growing number of studies have suggested that oxidative stress refers to the elevated production of intracellular ROS, which may lead to damage in tissue, lipids, proteins and dNA, involved in the pathophysiological processes of cerebral ischemia (37,38). It is well known that the antioxidant activity of curcumin is critical for its neuroprotective effects (39). APE1 is a master regulator of the cellular response to oxidative stress, and is involved in gene transcriptional regulation during the adaptive cellular response to oxidative stress, as well as in the base excision repair pathway of oxidative dNA lesions, which consist of dNA-protein crosslinks, AP sites, 8-OHdG formation and single-strand breaks (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…However, approved drugs for the treatment of cancer are usually limited by potential undesirable side effects such as hepatotoxicity, nephrotoxicity, ototoxicity, reduction in platelet counts, and myelosuppression . Curcumin, a natural polyphenolic compound and the principal coloring agent found in the rhizomes of Curcuma longa (Zingiberaceae), has several health benefits, including antioxidant , anti‐inflammatory , immunomodulatory , antiarthritic , antithrombotic , pulmonoprotective , lipid‐modifying , neuroprotective , anticancer , antidiabetic, and hepatoprotective properties. Numerous reports have indicated that curcumin is quite safe and nontoxic to humans up to doses of 12 g/day .…”
Section: Introductionmentioning
confidence: 99%